2022
DOI: 10.1136/bjsports-2022-105567
|View full text |Cite
|
Sign up to set email alerts
|

International Olympic Committee (IOC) consensus statement on acute respiratory illness in athletes part 2: non-infective acute respiratory illness

Abstract: Acute respiratory illness (ARill) is common and threatens the health of athletes. ARill in athletes forms a significant component of the work of Sport and Exercise Medicine (SEM) clinicians. The aim of this consensus is to provide the SEM clinician with an overview and practical clinical approach to non-infective ARill in athletes. The International Olympic Committee (IOC) Medical and Scientific Committee appointed an international consensus group to review ARill in athletes. Key areas of ARill in athletes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 172 publications
0
18
0
Order By: Relevance
“…However, only one had obstructive lung function at the time of examination, and the remaining 10 athletes with obstructive lung function after COVID-19 were not known to have asthma. The diagnosis of asthma can be difficult to establish, and studies have shown a higher prevalence of airway hyperresponsiveness and asthma (‘lower airway dysfunction’) when using objective testing methodology [ 40 , 41 ]. We have no information on how the diagnosis of asthma had been determined before entering our study, but one possible explanation for the high number of athletes with obstructive lung function could be that they had undiagnosed asthma before the COVID infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one had obstructive lung function at the time of examination, and the remaining 10 athletes with obstructive lung function after COVID-19 were not known to have asthma. The diagnosis of asthma can be difficult to establish, and studies have shown a higher prevalence of airway hyperresponsiveness and asthma (‘lower airway dysfunction’) when using objective testing methodology [ 40 , 41 ]. We have no information on how the diagnosis of asthma had been determined before entering our study, but one possible explanation for the high number of athletes with obstructive lung function could be that they had undiagnosed asthma before the COVID infection.…”
Section: Discussionmentioning
confidence: 99%
“…The International Olympic Committee (IOC) recently published a two-part consensus statement that covers acute respiratory infections 55 and non-infective acute respiratory illness. 56 The drive behind these statements is to provide guidance to sport and exercise science/medicine practitioners working with athletes and to uphold the Medical and Scientific Commission's value of protecting athletes, whilst focusing on prevention and management and enabling the development of effective return to sport protocols following acute illness. Data from the report highlights that almost half of all athlete's medical consultations at international events such as the Olympics and Para Olympics relate to acute respiratory illness (4.2 per 1000 athlete days).…”
Section: Sports Cardiology and Covid-19mentioning
confidence: 99%
“…Non-infective ARill was defined as an illness not caused by infection from a specific pathogen, by clinical diagnosis or laboratory investigation(s). There are several conditions that cause non-infective ARill and these are comprehensively reviewed in part 2 of the IOC Consensus statement on ARill in athletes 23…”
Section: Terminology Definitions and Classification Of Arinf In Athletesmentioning
confidence: 99%
“…(4,7,8,10,12) The aim of this consensus statement is to provide the SEM clinician with an overview and practical clinical approach to ARinf in athletes. This document forms Part 1 of a three-part series, with Part 2 focusing on non-infective acute respiratory illness in athletes (23) and Part 3 on SARS-CoV-2 infection in athletes. (24) The specific focus of Part 1 is to review clinically relevant aspects of ARinf in athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation